The role of lecturer in improving college quality learning - Guterres, Antonio; Goncalves, Agostinho dos Santos; Pereira, Sebastiao (International Journal of Innovative Research and Scientific Studies, 2025)
Lecturers are one of the essential components in universities, where their existence is very important, associated with roles, assignments, and responsibilities to achieve national education by transforming, developing, and disseminating science, technology, education, arts, research, and community service as the main tasks. Therefore, lecturers are required to have pedagogical, personality, social, and professional competencies that aim to describe their role in relation to the quality of learning in college. This exposure is expected to broaden the knowledge of lecturers and university policymakers to improve the quality of the learning process in order to produce quality graduates as well. The research methodology used was literature. This means that researchers utilized literature, either in the form of books, records, or reports of previous research results. In this study, there were four productivities through learning quality improvements: (1) Goal-Congruent Lecturers and College, (2) Learning System, (3) Lecturers’ Paradigm, and (4) College Objectives Quality. Therefore, lecturers are always trying to improve their knowledge. They can follow higher education, keep in touch with the latest technology, remain aware of their responsibility to help students become the best, and always strive to prepare the best learning lessons. Lecturers, as a determinant factor of learning quality, have the responsibility of being the organizers. To teach well, lecturers need to perform self-evaluation, integrated control, and act as educators and teachers, especially in higher education. Timor Leste is currently in development. The process of the lecturers requires a greater commitment from college management as well as support from the government in order to increase resources for sustainable human development that can meet the needs of quality and achievement, targeting the scope of competition and ensuring that implementation meets the requirements.